Pluriactivity and professionalism in buffalo farming system: The case of Northern Greece - TSIOBANI, E; HASANAGAS, N; YIAKOULAKI, M; PAPANIKOLAOU, K (The Indian Journal of Animal Sciences, 2013)
Pluriactivity and professionalism in the water buffalo farming system was investigated with standardized questionnaires and in-depth interviews with breeders at Lake Kerkini National Park, Greece, where 80% of the country’s buffalo population is raised. A distinction between total and complementary pluriactivity is proposed depending on including (or not) buffalo breeding as main occupation, respectively. Complementary pluriactivity appears to have synergistic effect and to encourage commerce of buffalo products to end users. Breeders not oriented to milk production tend to invest time in agriculture. Commerce seems to be encouraged by using private land for breeding (temporary pastures for early spring grazing and crop residues during summer-early autumn). Agriculture appears to be the usual alternative activity. The family character of holding and not the size of buffalo herd or the ownership status of agricultural land used for breeding seem to enhance professionalism. Simultaneous keeping of goat flocks and commerce weaken it.